(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
While well-known thought is that Article 35A and Article 370 give JK an extraordinary state status, the Center has comparable plans with a few others. We disclose the two rules to demystify the issue with hypothesis overflowing that the Bharatiya Janata Party - drove focal government could nullify or attempt to change Article 35A and article 370, which give an exceptional status to Jammu and Kashmir, there is a ton of perplexity regarding what these two rules involve. Ideological groups on either side of the discussion have voiced their assessment, with some calling tinkering with Article 35A like setting powder barrel ablaze, while others have bolstered the thought considering it a transition to bring together of the nation.